Brivaracetam: Rationale for discovery and preclinical profile of a selective SV2A ligand for epilepsy treatment. (26th February 2016) - Klitgaard, Henrik; Matagne, Alain; Nicolas, Jean‐Marie; Gillard, Michel; Lamberty, Yves; De Ryck, Marc; Kaminski, Rafal M.; Leclercq, Karine; Niespodziany, Isabelle; Wolff, Christian; Wood, Martyn; Hannestad, Jonas; et al.
Summary: Despite availability of effective antiepileptic drugs (AEDs), many patients with epilepsy continue to experience refractory seizures and adverse events. Achievement of better seizure control and fewer side effects is key to improving quality of life. This review describes the rationale for the discovery and preclinical profile of brivaracetam (BRV), currently under regulatory review as adjunctive therapy for adults with partial‐onset seizures. The discovery of BRV was triggered by the novel mechanism of action and atypical properties of levetiracetam (LEV) in preclinical seizure and epilepsy models. LEV is associated with several mechanisms that may contribute to its antiepileptic properties and adverse effect profile. Early findings observed a moderate affinity for a unique brain‐specific LEV binding site (LBS) that correlated with anticonvulsant effects in animal models of epilepsy. This provided a promising molecular target and rationale for identifying selective, high‐affinity ligands for LBS with potential for improved antiepileptic properties. The later discovery that synaptic vesicle protein 2A (SV2A) was the molecular correlate of LBS confirmed the novelty of the target. A drug discovery program resulted in the identification of anticonvulsants, comprising two distinct families of high‐affinity SV2A ligands possessing different pharmacologic properties. Among these, BRV differed significantly from LEV by its selective, high affinity and differential interaction with SV2A as well as a higher lipophilicity, correlating with more potent and complete seizure suppression, as well as a more rapid brain penetration in preclinical models. Initial studies in animal models also revealed BRV had a greater antiepileptogenic potential than LEV. These properties of BRV highlight its promising potential as an AED that might provide broad‐spectrum efficacy, associated with a promising tolerability profile and a fast onset of action. BRV represents the first selective SV2A ligand for epilepsy treatment and may add a significant contribution to the existing armamentarium of AEDs.